TAHLIL AL-NUSUS AL-MA’ANI FI SURAH AL-FATHI WA TATBIQUHA FI TA’LIM AL-LUGHAH AL-‘ARABIYAH LADA THULLAB BI MADRASAH HUSNUL ABRAR AL-DINIYYAH AL-ISLAMIYYAH KETANGGA LUMBUK AL-SYARQIYAH - Anshari, M Sauqi Sufyan; Maujud, Fathul (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
Muslims believe that learning Arabic should be primarily focused on understanding the meaning of the Qur'anic texts because the Arabic language and the al-Qur'an have a close link. Understanding the meaning of the Qur'an requires knowledge of both the inner uses of the sentences as well as the actual lafaz from which they are constructed. Also, because it uses instances of expressions quoted from the Qur'an, Arabic language study has not been centered on developing student talents in understanding the meaning of the Qur'an from the perspective of Balagah Science. This study employs a descriptive qualitative research design, and two methodologies are used to collect the data. A direct analysis of the Balagah Surah Al-Fath employing Balagah Science Theories Library Research is the first technique, in which researchers gather information by looking at the well-known interpretation books among Muslims. The researcher collects data, which is involves direct observation, and interviews in the research field. There are goals for this investigation is to make these methods more effective for learning Arabic. Based on the findings of the study process conducted at Madrasah Diniyah Islamiyah Ketangga, it has been determined that the surah Al-Fath contains a number of Balagiyah Techniques, including 1. Ijaz (4), 2. Ithnab (5), and 3. Musawah (1). The Qiasiyah Method is used to implement these Balagiyah Techniques, which starts with a general Qawa'id Balagiyah lesson before introducing examples from surah Al-Fath as a way to compare them to the Qowa'id and to help students understand it better.